Statement by the Managing Director on the Work Program of the Executive Board : Executive Board Meeting, November 22, 2010. (Policy Papers; Policy Paper, 2010)
Persistent challenges: The multi-speed nature of the global economic recovery is testing the system, with strains already appearing in the form of large capital inflows to many emerging market countries and exchange rate pressures. At the same time, slow employment growth, high indebtedness, and remaining financial sector fragilities in some countries could yet derail a fragile recovery. Only cooperative approaches will succeed in relieving tensions and building a strong and sustainable recovery, based on a more balanced pattern of global growth.